Was Keynes a "Keynesian"? A Review Article - Grossman, Herschel I. (Journal of Economic Literature, 1972)
AXEL LEIJONHUFVUD has recently provided us with an insightful and refreshing reappraisal of the so-called revolution in his On Economics and the Economics of Keynes [8, 1968]. In light of the significance and importance of this book, it is disappointing that, although the reviewers have been very complimentary, the published discussion seems to have offered little in the way of critical evaluation of Leijonhufvud's arguments. This paper attempts to remedy this situation. Leijonhufvud argues convincingly that popular Keynesianism, as well as its offspring, the so-called neoclassical synthesis, does not have an adequate choice-theoretic, i.e., microeconomic, basis. This view seems to be finding wide and warranted acceptance. In addition, Leijonhufvud argues that, although this defect pervades popular Keynesianism, it does not characterize Keynes' own writings. Leijonhufvud suggests that Keynes himself would have been unsympathetic with the development of popular Keynesian macroeconomic theory. This paper argues, to the contrary, that this latter contention is not consistent with a complete and careful reading of the General theory. My analysis will suggest that Keynes' thinking was both substantially in accord with that of his popularizers and similarly deficient. Leijonhufvud's argument emphasizes the interpretation of the consumption function developed by R. W. Clower in his The Counter-Revolution: A Theoretical Appraisal [3, 1965]. I certainly accept Leiionhufvud's contention that Clower's conception, which is discussed more fully below, provides the choice-theoretic basis for macroeconomic theory, which popular Keynesianism lacks.' However, Leijonhufvud also suggests that Clower's conception may be attributed to Keynes himself.2 This latter is the hypothesis at issue. Leijonhufvud can point to no specific content in Keynes' writing which explicitly supports this attribution. His argument (pp. 91-102) seems to amount to the following: Keynes' discussion is dreadfully confusing, but Clower's interpretation offers the only conceivable way to make sense of it.3 Therefore, Keynes must have had Clower's idea in mind. My analysis will focus upon Keynes' treatment of the demand for labor services, a part